Mediating Contribution of Job Crafting to the Role of Servant Leadership and AI in Enhancing Work Engagement - Mey Ayu Lestari; Ardiani Ika Sulistyawati; Gehad Mohammed Sultan Saif (Inovasi Analisis Data, 2024)
Objective: This study investigates the mediating role of job crafting in the relationship between artificial intelligence (AI) awareness, servant leadership, and work engagement among employees.Methods: Utilizing quantitative analysis, the research involved surveying employees and employing structural equation modeling to test the proposed hypotheses regarding the influence of AI awareness and servant leadership on job crafting and work engagement.Findings: The results reveal that while servant leadership significantly enhances job crafting and work engagement, AI awareness does not positively impact job crafting. However, job crafting positively influences work engagement and mediates the effect of servant leadership on work engagement, indicating a complex interplay between leadership styles and employee engagement levels.Novelty: This study contributes to the literature by highlighting the differential impact of AI awareness and servant leadership on job crafting and work engagement, emphasizing the critical role of leadership in fostering employee motivation and productivity in the context of technological advancements.Theory and Policy Implications: The findings suggest that organizations should focus on developing servant leadership qualities among managers to promote job crafting and enhance employee engagement. Furthermore, while fostering AI awareness is essential, organizations must balance it with supportive leadership practices to prevent potential negative impacts on employee morale.